BLAMING THE VICTIM : OBJEKTIFIKASI KORBAN KEKERASAN SEKSUAL DALAM PEMBERITAAN DI MEDIA ONLINE BALAIRUNGPRESS.COM - Faatihah Dhuha Najib; Sunarto . (Interaksi Online, 2020)
Textual in this news is very interesting to study because it intersects with feminism as well as discussing controversy in the representation of victims, the purpose of this study is to find out the audience's meaning to the news "Nalar Pincang UGM atas Kasus Perkosaan". In addition, this study also reveals the motivation of the Balairung newsroom in raising news and analysis of socio-cultural conditions that influence every action and decision making that is created in the Balairung newsroom. The research method used in this study is Critical Discourse Analysis and focuses the research at three stages, namely the micro, meso, and macro levels. At the micro level, the composition of the coverage that includes chronology as a discussion becomes an instrument that leads to the sexual objectification of pornography / eroticism. The use of diction is used to cause news bias because the victim is again positioned as 'victim'. Biased diction that is often used to describe the rape event carried out, namely "touching the chest", "kissing the lips", "touching and inserting his finger". The use of the diction means to equate the victim as an object that is indeed worth exploring what behavior her body receives. The results of research at the meso level using reception analysis include two things, namely the practice of producing and consuming texts. This level of research reveals the transfer of moral ethics and social considerations in addressing cases of sexual violence itself. The reason for determining the sources also contributed to assumptions in the imbalance and credibility of the news. Critics and evaluations from the audience were not used as evaluations by the newsroom itself. In fact, in its editorial, the affirmation of attitude not to require evaluation becomes the controversial closing commentary of the news release. It did not stop there, the reproduction of texts consumed by other mass media such as Tempo and VOA even alienated victims as informants in the news. After that, the results of research at the macro level include violations that have been committed by Pedoman Pemberitaan Siber that serve as a reference in the editorship. In fact, UGM itself has not been able to formulate laws governing the handling of cases of sexual violence in the campus environment, so it is very possible that the practice of journalism that is not victim-friendly is also caused due to the inequality of frames and values believed by the UGM entity itself, both from the Rectorate, victims (in this case students), or even press institutions from UGM. Research implications are manifested in theoretical, practical and social forms. Recommendations from this research are gender awareness in a mass media newsroom institution in order to provide adequate understanding to all workers, both men and women, of the importance of creating symmetrical and fair gender relations in representation by paying attention to the creation of news that understands packaging that actually really defend and protect victims.